Association of Lipid Profile and Suicide Attempts in a Large Sample of First Episode Drug-Naive Patients With Major Depressive Disorder - Ma, Yue-Jiao; Zhou, Yong-Jie; Wang, Dong-Fang; Li, Yi; Wang, Dong-Mei; Liu, Tie-Qiao; Zhang, Xiang-Yang (Frontiers in Psychiatry, 2020)
Several studies have reported a link between lipid disorders and suicidality. However, few studies have investigated the relationship between suicidal behavior and blood lipid profiles in patients with first-episode and drug-naive (FEDN) major depressive disorder (MDD). The main purpose of this study was to examine the relationship between plasma lipid profiles and suicide attempts in a large sample of FEDN MDD patients in the Chinese Han population, which has not been reported. A total of 1718 MDD outpatients were recruited. Their clinical and demographic data as well as plasma lipid parameters were collected. We obtained suicide attempt data through interviews with patients and their family members. We rated the Hamilton Depression Scale (HAMD) and Hamilton Anxiety Scale (HAMA) for all patients. The suicide attempt rate of MDD patients was 20.14%, of which 13.68% in the last month and 6.46% in the past. Further, compared with non-attempters, suicide attempters had significantly higher total levels of cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c), higher HAMA and HAMD scores, but significantly lower high-density lipoprotein cholesterol (HDL-c) levels. Logistic regression analysis showed that suicide attempts were correlated with higher TC, lower HDL-c, and higher HAMA and HAMD scores with the adjusted odds ratio (OR) of 1.35, 0.52,1.28 and 1.08, respectively (all p<0.05). Our findings suggest that FEDN patients with MDD have a high rate of attempted suicide. In the early stage of MDD patients, certain blood lipid parameters and more severe symptoms of anxiety and depression are correlated with suicide attempts. However, due to the cross-sectional design of this study, it is impossible to draw a causal relationship between lipid profiles and suicide attempts. Moreover, an inverse correlation can also be considered, that is, high cholesterol may be the consequence of suicide attempts and depression.